Distance running in hot environments: a thermal challenge to the elite runner - Maughan, R. J. (Scandinavian Journal of Medicine & Science in Sports, 2010)
Endurance performance is impaired in the heat, and a combination of high temperature and high humidity presents a major challenge to the elite marathon runner, who must sustain a high metabolic rate throughout the race. The optimum temperature for marathon performance is generally about 10-12 °C. The optimum temperature may be lower for faster runners than for slower runners. Sweat evaporation limits the rise in core temperature, but dehydration will impair cardiovascular function, leading to a fall in blood flow to muscle, skin and other tissues. There is growing evidence that the effects of high ambient temperature and dehydration on performance of exercise may be mediated by effects on the central nervous system. This seems to involve serotonergic and dopaminergic functions.